Lignin Extraction for a Better Fractionation of Raw Lignocellulosic Biomass Pretreatment for Energy Production - Siddique,Mohammad (2024)
Abstract One of the most frequently produced agricultural wastes is is biomass, from which lignin is obtained. It contains a high concentration of Ln, Cs and Hcs. It is one of the main sources of energy in the globe, but is underutilized. To extract Ln from plants using acid pretreatment and alkali, the current research employed a biomass resource that is easily accessible. Ln was extracted from four different Bm: AS, BTB, NTB and WS. The proximate and final analyses were utilized to describe Ln after the pretreatment procedure. NTB had the lowest S content. Analysis of TGA test for Bm from Lc was performed. BTB had the highest projected Ct of Ln recovery, at 100 ºC. NTB produced a minimum Ln amount of 6%, compared to 8% yield from BTB, after 5 h. Ln yield at 160 ºC was lower. WS and AS had the same Ln yield (7%), after 5 h. The extracted Ln, which has a higher phenolic content than that from the commercial one, can be used in future applications.